Paciente masculino de 85 años con insuficiencia respiratoria aguda. - Rodríguez Chevez, Yoselin Xiomara (2021)
In the present clinical case study, it refers to an adult patient over 85 years of age, male, with a married marital status, with a primary school level, of medium socioeconomic level, who lives in the city of Vinces, has a previous pathological history of arterial hypertension, in the last hours he presented a picture compatible with respiratory failure so he enters the Emergency at the Dr. Nicolás Coto Infante Basic Hospital, he is taken by his granddaughter with symptoms such as: dyspnea, dry cough, fever, fatigue, insomnia. Once admitted, he was treated according to the presumptive diagnosis and due to the presence of cyanotic skin and 94% saturation, for which oxygen therapy is applied, with a nasal cannula at 3 liters per minute along with 10mg enalapril, to have the diagnosis final chest X-ray, laboratory tests, chest CT, electrocardiogram, the patient presented acute respiratory failure due to heart failure. The patient was admitted to the Dr. Nicolás Coto Infante Basic Hospital in the observation area, where the doctor and the respiratory therapist apply different treatments for the recovery of the patient, who was hospitalized for 13 days, after which exercises are recommended. to recover lung capacity among other activities that includes outpatient care with the cardiologist.